Evaluation of prevalence of hypertension and diabetes and its risk factors in a patients coming to the rural health training centre in district Panvel of Maharashtra - Gethe, Rahul (International Journal Of Community Medicine And Public Health, 2019)
Background: A systematic review done by Anchala et al concluded that one-third of urban adult Indians and close to one fourth of rural adult Indians are hypertensive. Overall prevalence of hypertension (HTN) in India, after weighting the regional population size, was 29.8%. As of 2014, 8.3% of the world’s adult population suffered from diabetes, with low-income countries in Africa and Asia bearing the brunt of this burden. Objectives of this study were to evaluate the prevalence of hypertension and diabetes in patients coming to the rural health training centre (RHTC). To find out the association of selected risk factors with hypertension and diabetes. Methods: It was a cross sectional study conducted in RHTC, Panvel Maharashtra in July 2019 (1 month) with sample size of 300. Results: A total 133 patients had normal BMI, 124 were overweight and 48 were obese Out of total patients, 222 had normal blood pressure, 46 were pre- hypertensive and 32 were hypertensive. 42 patients had random blood glucose level more than 200 mg/dl. Conclusions: There was association of body mass index, age and sex with both hypertension and high blood sugar level whereas association of addiction was present with high blood sugar level.